1990
DOI: 10.1002/tcm.1770100104
|View full text |Cite
|
Sign up to set email alerts
|

Preparation for Human Study of Pesticide Applicators: Sister Chromatid Exchanges and Chromosome Aberrations in Cultured Human Lymphocytes Exposed to Selected Fumigants

Abstract: In preparation for a human study of worker exposure to grain fumigants and pesticides, we decided to screen commonly used fumigants for genotoxic effects in vitro. This research strategy was employed to test the possibility that structurally simple chemicals might have similar genotoxic properties in vivo and in vitro. As a first step, we designed our in vitro protocol to mimic to the extent possible, a single in vivo exposure of lymphocytes to fumigants. Go lymphocytes were treated with different doses of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 26 publications
(17 reference statements)
1
13
0
1
Order By: Relevance
“…But, it was also reported that fumigant applicators were exposed to PH(3) had significantly increased CA and SCE rates in lymphocytes. [22] Our findings also revealed that AIP lead to oxidative damage on cultured human blood cells. In this study, AIP caused increase of TOS level and decrease of TAC level as compared to control group.…”
Section: Discussionsupporting
confidence: 57%
“…But, it was also reported that fumigant applicators were exposed to PH(3) had significantly increased CA and SCE rates in lymphocytes. [22] Our findings also revealed that AIP lead to oxidative damage on cultured human blood cells. In this study, AIP caused increase of TOS level and decrease of TAC level as compared to control group.…”
Section: Discussionsupporting
confidence: 57%
“…They also considered that the conclusions from these animal experiments could not be extrapolated to human non-conjugators, since these particular individuals are unable to metabolize methyl bromide as quickly as a rodent can [24]. Other studies report pre-carcinogenic sister chromatid exchange and the induction of chromosome aberrations after exposure to methyl bromide [53,54]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that malathion induced complex structural chromosomal aberrations in whole human blood cells in the presence of S9 mix [29].…”
Section: Discussionmentioning
confidence: 99%